2022
DOI: 10.32794/mr112500127
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits Zika virus replication in Vero epithelial cells and SK-N-SH human neuroblastoma cells

Abstract: Zika virus (ZIKV) is an emerging flavivirus that is causing significant public health concerns worldwide because of its association with severe neurological disorders in both newborns and adults. At present, the search for effective antiviral drugs for ZIKV infection is intense. Melatonin is a molecule that influences a wide variety of physiological processes. Melatonin is a direct free radical scavenger, an indirect antioxidant due to its stimulation of antioxidant enzymes and an anti-inflammatory and immunor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, doses of melatonin below CC 50 values, including 125, 250 and 500 μM, that exhibited greater than 90% cell viability were selected for further studies on antiviral effects. Our selected doses were the same as those previously used in the in vitro studies on antiviral effects of melatonin against other virus types [25][26][27][28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, doses of melatonin below CC 50 values, including 125, 250 and 500 μM, that exhibited greater than 90% cell viability were selected for further studies on antiviral effects. Our selected doses were the same as those previously used in the in vitro studies on antiviral effects of melatonin against other virus types [25][26][27][28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…The time-of-addition assay indicated that melatonin exerted the major inhibitory activity on the post-entry step of the JEV replication cycle; this was demonstrated by the significant reduction of JEV yield when the cells were treated after infection, but not before or during infection. In this study, the concentration of melatonin was chosen based on our cytotoxicity assessment and previous in vitro studies of the antiviral effect of melatonin against several viruses; these values were between 0.1 and 1.2 mM in different types of cell lines [25][26][27][28][29][30][31] . Previous studies have demonstrated the protective effect of melatonin at 0.1-1 mM against toxic substance-induced cytotoxicity, oxidative stress, and apoptosis in neuronal and other cells [35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports were published within a month of each other and both showed that melatonin is a significant factor in inhibiting a Zika infection in cultured cells. In the most complete study, Wongchitrat and co‐workers 7 found that melatonin reduced viral replication in both Vero and SK‐N‐SH cells in a time and dose‐dependent manner with the protection being more obvious in the human SK‐N‐SH cells. With the aid of a molecular docking technique, the authors also showed that melatonin had a high binding affinity to the nonstructural protein (NS3) of the virus; this may be a mechanism by which melatonin inhibits the Zika infection.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin, with its well-established safety profile and accessible availability, attracted attention as a potential adjunctive therapy for COVID-19. [7][8][9][10][11] Preliminary evidence suggests that melatonin may play a multifaceted role in combating the virus, including inhibiting viral replication, mitigating excessive inflammation, and enhancing immune response. However, despite promising findings, the true extent of melatonin's antiviral efficacy and its potential application in the broader context of viral infections require further exploration.…”
mentioning
confidence: 99%